ORTHOREXIA AND EATING ATTITUDES IN HEALTH SCIENCES STUDENTS: ORTHOREXIA IN HEALTH SCIENCES STUDENTS - ÇAĞIRAN YILMAZ, Feray (European Journal of Applied Sciences, 2021)
Background: Investigating eating disorders and orthorexia nervosa, especially in the young population, is an important step in taking protective precautions and identifying disease Objective: To Investigate the incidence of disordered eating attitudes and orthorexia tendencies in among university students studying in various Health Sciences departments in Turkey. Methods: A total of 639 second and third year university students participated in this study. The EAT-40 and ORTO-15 that are validated instruments for the screening of abnormal eating behaviors and orthorexia nervosa respectively, were used as measurement tools. Results: Majority of the students who participated in the study were found to exhibit orthorexic tendency, and that male students had a more orthorexic tendency in comparison to female students (p = 0.022). More specifically, the students studying in the Department of Nutrition and Dietetics had lower orthorexic tendencies compared with the students from other departments. There was no significant relationship between BMI values and the mean ORTO-15 scores, whereas the mean EAT-40 score was found to increase statistically significantly with increased BMI (p = 0.038). There was a statistically significant difference between the departments and classes in terms of mean EAT-40 scores, whereas no difference was found regarding gender. Conclusion: All students except the Nutrition and Dietetics department show orthorexic tendency. The EAT-40 scores of the participants were 16.0 (low risk) for the whole sample. More comprehensive studies are needed to better understand the orthorexia nervosa and healthy lifestyle interaction.